PENGARUH PIJAT LAKTASI TERHADAP PRODUKSI ASI PADA IBU MENYUSUI DI PMB BD M KOTA DEPOK TAHUN 2023 - Yusti, Eli (Politeknik Tiara Bunda, 2023)
Breast milk production in breastfeeding mothers typically ranges from 750 ml to 1,000 ml per day. Therefore, breastfeeding mothers need complementary care to facilitate milk production to ensure that the baby’s needs are met. One of the complementary care methods that can be used is lactation massage, as it can prevent milk duct blockages and help improve milk flow. The aim of this study is to determine the effect of lactation massage on breast milk production in breastfeeding mothers before and after the intervention. The method used is a quasi-experimental design with a pretest-posttest design without a control group. The study sample consisted of 15 breastfeeding mothers, and the Wilcoxon statistical test was used. The results showed that there is an effect of lactation massage on increasing breast milk production after the massage intervention, with a significant increase in milk production (p-value = 0.00 < 0.05). Lactation massage can directly benefit breastfeeding mothers who have low or insufficient milk flow. Therefore, it is recommended to provide education on the effects of lactation massage on milk production in breastfeeding mothers and to offer more in-depth education on lactation massage techniques through classes or special sessions provided by healthcare professionals.